POSTER DESIGN PLANNING TO INCREASE COMMUNITY MOTIVATION IN USING THE SATU SEHAT APPLICATION AT HARAPAN BUNDA CLINIC NGAMPEL - Amanda Nadylla Kustina; Rumpiati Rumpiati (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
The Satu Sehat application was developed as an integrated electronic medical record platform to support digital transformation in healthcare services. However, limited public awareness and the absence of visual promotional media at Harapan Bunda Clinic Ngampel have resulted in low application usage. Therefore, this study aimed to design a poster that could increase community motivation to use the Satu Sehat application. The study was conducted at Harapan Bunda Clinic Ngampel from April to May 2025. Participants included clinic staff, patients or family members, and a design expert. This study employed a Research and Development method using the 3D model, consisting of Define, Design, and Development stages. The Define stage focused on identifying user needs, the Design stage involved creating the poster, and the Development stage included product testing and revision. The results showed that the poster contained essential information about Satu Sehat and was effective as a promotional medium. Validation scores from clinic staff and the design expert were 84.28% and 90%, respectively, both categorized as good. The poster was considered attractive, easy to understand, and capable of increasing public motivation. In conclusion, the poster effectively conveyed information visually and can support communication strategies for healthcare digitalization at the clinic.